Upaya Kepolisian dalam Penanggulangan Penyalahgunaan Narkotika (Studi Kasus di Polres Luwu) - Abdianto; Takdir; Assaad, Andi Sukmawati; Umar, Nasaruddin (LP2M IAIN Palopo, 2024)
This study aims to understand the police efforts in overcoming drug abuse that occurs in the working area of the Luwu Resort Police, factors that become obstacles in efforts to overcome drug abuse and efforts to overcome drug abuse by the Luwu Resort Police. A qualitative method was implemented in this research, using observation, interview, and documentation techniques as instruments. Researchers used data reduction techniques, data presentation, descriptive analysis, and conclusion drawing to analyse the data. The data shows that the efforts to overcome drug abuse by the Luwu Resort Police involve members of the Luwu Resort Police Narcotics Unit who are active in preventing the eradication of abuse, as well as the illicit circulation of Narcotics in the Luwu Resort Police Legal Area. In addition, the police guard places with access to transportation from one region or country to another and form a Drug-Free Village. It is hoped that there will be support from all levels of society in Luwu Regency to fully support the implementation of countermeasures carried out by the Luwu Resort Police so that the circulation and abuse of Narcotics can be immediately overcome and reduce the victims arising from the abuse of Narcotics. Efforts to eradicate and enforce the law must be carried out more firmly; this is intended so that the perpetrators of narcotics crimes feel a deterrent and no longer repeat their actions due to the application of coercive sanctions following the criminal threats contained in Law No. 35 of 2009 concerning Narcotics. Keywords: Countermeasures, Abuse, Narcotics